THE ROLE OF CONTENT QUALITY AND THE INFLUENCE OF SOCIAL MEDIA, INFLUENCERS ON PURCHASING DECISIONS MEDIATED BY THE SHOPEE E- WOM PLATFORM FOR FASHION PRODUCTS - Trida Trisno Zuono; Abdul Halik, Estik Hari Prastiwi (CV. Adiba Aisha Amira, 2025)
In the rapidly evolving digital landscape, E-commerce platforms, particularly in the fashion sector, are gaining increasing prominence. Shopee, as a leading E- commerce platform, provides a diverse array of fashion products from various brands and sellers. This study adopts a quantitative research approach to validate pre-established hypotheses. The chosen research method involves a survey utilizing a questionnaire. The population under consideration consists of subjects affiliated with the research conducted on the Shopee marketplace, with respondents being consumers of the Regalia Garment shop. A purposive sampling technique was employed, with 150 respondents selected based on their high shopping frequency on the Shopee platform. Hypothesis testing in this research employs a Structural Equation Model (SEM) approach, specifically based on Partial Least Square (PLS). The study delves into the influence of content creators, social media, and influencers on purchasing decisions for fashion products on Shopee. The results of the hypothesis analysis reveal a complex landscape concerning the interaction variables within the realm of digital marketing on the Shopee platform that impact decision-making. While social media may not exhibit a significant influence on purchasing decisions on Shopee, various other indicators on the platform suggest an impact on social media variables. Notably, optimizing marketing strategies that leverage the role of influencers in appropriate product contexts demonstrates a positive and significant influence on purchasing decisions. Furthermore, it is evident that social media positively affects Electronic Word-of-Mouth (e-WOM) by influencing trends and fostering conversations that impact its audience. In the e-commerce landscape, influencers play a crucial role, exerting influence through interactions and recommendations to their followers, thereby influencing individual purchasing decisions. The significance of e-WOM in shaping purchasing decisions on Shopee is underscored by recommendations from numerous users, even though it may not have a statistically significant impact on purchasing decisions in certain aspects.